2020
DOI: 10.3390/agriculture10060218
|View full text |Cite
|
Sign up to set email alerts
|

Identification Process of Selected Graphic Features Apple Tree Pests by Neural Models Type MLP, RBF and DNN

Abstract: In this paper, the classification capabilities of perceptron and radial neural networks are compared using the identification of selected pests feeding in apple tree orchards in Poland as an example. The goal of the study was the neural separation of five selected apple tree orchard pests. The classification was based on graphical information coded as selected characteristic features of the pests, presented in digital images. In the paper, MLP (MultiLayer Perceptrons), RBF (Radial Basis Function) and DNN (Deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Currently, one of the most modern techniques of image processing [ 19 , 20 ] and image classification [ 21 , 22 ] in decision-making processes is the use of artificial intelligence methods [ 23 , 24 ]. In recent years, artificial neural networks have become so popular and effective that they started to be used in various problematic areas, among other things, in the optimization of food processes [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, one of the most modern techniques of image processing [ 19 , 20 ] and image classification [ 21 , 22 ] in decision-making processes is the use of artificial intelligence methods [ 23 , 24 ]. In recent years, artificial neural networks have become so popular and effective that they started to be used in various problematic areas, among other things, in the optimization of food processes [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows that MLP benefits from a three-layer structure, including the input layer, hidden layer/s, and output layer/s, in which each neuron is connected to all the neurons in the next layer. It is frequently reported that MLP has a great function in non-linear problems [46,47].…”
Section: Mlpmentioning
confidence: 99%
“…Figure 2 shows that MLP benefits from a three-layer structure, including the input layer, hidden layer/s, and output layer/s, in which each neuron is connected to all the neurons in the next layer. It is frequently reported that MLP has a great function in non-linear problems [46,47]. where I represent the input layer, Ii is the input variable i, n shows the total number of inputs, βj is a bias value, and ωij is the weight of connections in j level.…”
Section: Mlpmentioning
confidence: 99%
“…Figure 2 shows that MLP benefits from a three-layer structure, including the input layer, hidden layer/s, and output layer/s, in which each neuron is connected to all the neurons in the next layer. It is frequently reported that MLP has a great function in non-linear problems [49][50]. (1) Where I represent the input layer, Ii is the input variable i, n shows the total number of inputs, βj is a bias value, ωij is the weight of connections in j level.…”
Section: Mlpmentioning
confidence: 99%